2012
DOI: 10.1590/s0103-50532012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the catalyzed photo-cold vapour generation for determination of mercury by AAS

Abstract: Nanopartículas de Ag suportadas em TiO 2 (Ag-TiO 2 ) foram usadas como catalisador na geração de vapor frio induzida por radiação UV com ácido fórmico, acoplado à absorção atômica para determinação do mercúrio total em amostras analíticas. A atividade redutora de Ag-TiO 2 foi comparada com dois catalisadores semicondutores: TiO 2 não modificado e ZnO. O efeito do tipo de catalisador, sua concentração na amostra analisada, pH da amostra, concentração do ácido fórmico e tempo de irradiação ultravioleta foi inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The greatest number of publications is on PVG of Hg. Hou et al 84 Matusiewicz et al 86 used Ag nano-particles immobilised on TiO 2 to act as a catalyst for PVG of Hg in the presence of formic acid, and found that it offered improved performance compared with undoped TiO 2 and ZnO. They achieved from 95 to 99 % recoveries from…”
Section: Photochemical Vapour Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The greatest number of publications is on PVG of Hg. Hou et al 84 Matusiewicz et al 86 used Ag nano-particles immobilised on TiO 2 to act as a catalyst for PVG of Hg in the presence of formic acid, and found that it offered improved performance compared with undoped TiO 2 and ZnO. They achieved from 95 to 99 % recoveries from…”
Section: Photochemical Vapour Generationmentioning
confidence: 99%
“…After recent improvements in the analysis of Ge isotopes, the research community have collaborated on an inter-laboratory study to redefine approaches and improve data intercomparison. 193 They have defined a new delta-zero reference material for Ge in an existing CRM of ready supply (NIST SRM 3120a), settled on a common delta notation form This was repeated three times and nano-SIMS was used to construct 86 Sr/ 44 Ca maps at the sub-µm scale to record the ultrastructural details and growth histories of scleractinian corals.…”
Section: Environmental and Bioanalytical Sciencementioning
confidence: 99%
“…Calomel formation from PMC under nitrogen supported the two successive one-electron transfer reactions hypothesis, as in the case of inorganic salts. Other authors [215] studied Hg concentration, pH, formic acid concentration, the effect of oxygen, and UV irradiation time for this process. Chemical vapor generation (CVg) is used as a sample introduction method for specific trace element determination using atomic spectrometry [213].…”
Section: Mercurymentioning
confidence: 99%
“…Can be highlighted due to low operational cost, since the plasma is maintained through nitrogen removed from the atmospheric air and does not require flammable or expensive gases such as acetylene, nitrous oxide or argon, besides exhibits limits of detection close to the techniques of flame atomic absorption spectrometry (FAAS) and inductively coupled plasma optical emission spectrometry (ICP-OES). [17][18][19][20] The sample preparation is the most important step of a chemical analysis and there is no universal procedure that can be used in samples of different compositions. Thus, it is typical of the field of analytical chemistry to perform sequential studies on new systems and/or sample preparation methods in order to expand their working capacity.…”
Section: Introductionmentioning
confidence: 99%